Efecto de azospirillum spp. nativas en el desarrollo vegetativo de zea mays l. "maiz", en invernadero - Córdova Rojas, Lizbeth Maribel (2016)
The rizobacterias promoters of growth in plants are biofertilizers for agricultural crops, reducing the use of synthetic fertilizers. A trial was conducted With the objective of determining the effect of ten crops of Azospirillum spp. native to the height, aerial biomass and root of Zea mays L. "maíz" in greenhouse conditions. The previously isolated bacteria in the rizósfera of maize, were grown in nutritive broth for 24 hours and with the supernatant was obtained the inoculant standardized to 9 x 108 celmL-1, which was planted in broth soil extract 10%, tripticasa soya broth supplemented with tryptophan and broth Sundara Rao and Sinha Medium, to quantify the nitrogen fixed, indolacetic acid produced and phosphorus solubilised, respectively. In the greenhouse, the test was conducted as a completely random design with twelve treatments ten corresponding to the crops of Azospirillum, a chemical control (240N:80P:80K) and an absolute control (distilled water). The bacterial inoculum (4mL per seedling) was applied in the rhizosphere of corn seedlings, 7 days after sowing. The ten crops of Azospirillum spp. native fixed nitrogen as ammonium (3,2-32,1ppm), produced indolacetic acid (2,8-35,3ppm) and solubilized phosphorus (0,05-3,41ppm), highlighting Azospirillum sp. 77 in nitrogen fixation (32,10ppm) and production of indolacetic acid (35.3ppm) and Azospirillum sp. 65 in the solubilization of phosphorus (3.41 ppm). The ten crops of Azospirillum increased the height (IE=0,73-13,75%) and aerial biomass (IE=18,86-23,34%). In addition, eight crops of Azospirillum spp. increased root biomass (IE= 10,79-63,31%). Azospirillum sp. 65 exceeded the witness chemical in the EI in height at 25 and 50 days, aerial and root biomass to 75 days. Azospirillum spp. potential was demonstrated to increase vegetative growth in corn cultivation